Deep Fading Effect On an Individual Link of 4 × 4 Mimo Communication Systems - Mohammed Salemdeeb; Ammar Abu-Hudrouss (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The hottest issue of next generation communication systems is data throughput improvement for any wireless channel conditions. Multi-Input Multi-Output (MIMO) systems are the key technology for the next generation communication systems. Bill Lab Layered Space Time (BLAST) system achieves high data rates with acceptable BER performance over a good channels state. However, when the wireless channel has a considerable fading then the performance will be decreased and at a deep-fading state the system may fail to transmit any signal. This paper studies and compares the conventional 4 × 4 Vertical BLAST system capacity and bit error rate (BER) performance at Maximum Likelihood (ML) receiver through a simulation. It also studies the effect of a transmit-link deep-fading on the effective signal to noise ratio, system BER and system capacity in 4 × 4 VBLAST system in a comparative way with the conventional 4× 4, 3× 4, 2× 4 and 1× 4 VBLAST system. Considering that every possible case of transmit link deep fade lower than -20dB fading gain is equivalent to switching off this transmit link and mostly all of its power will be wasted. MATLAB software has been used as the main platform for system simulation.